Why gender focal person structures are not working in Rwanda and Uganda's national agricultural research organizations - Mangheni, Margaret Najjingo (GREAT, 2019)
Presented by Margaret Mangheni (GREAT), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.